"Love You, Bro": Performing Homosocial Intimacies on Twitch. (July 2022) - Welch, Tom
This article will consider the affective labor of male professional game streamers on Twitch in their role as performers and as community managers for their audiences. It asks what changes when we frame the discussion of male streaming labor around affect, and what is gained from thinking about streaming labor as a product and producer of norms and desires. Though a growing number of scholars have considered the roles of labor generally and affective labor in particular on Twitch, less attention has been spent on the particular role of masculinity in a space where the majority of streamers and viewers are male. This paper argues that male Twitch streamers ought to be understood as performing an inherently intimate and affective relational labor that produces and is produced by homosocial desire and the reification of geek masculinity, in addition to the affective labor of performance.